Two-Dimensional Van Der Waals Materials for Spin-Orbit Torque Applications - Tian, Mingming; Zhu, Yonghui; Jalali, Milad; Jiang, Wei; Liang, Jian; Huang, Zhaocong; Chen, Qian; Zeng, Zhongming; Zhai, Ya (Frontiers in Nanotechnology, 2021)
Spin-orbit torque (SOT) provides an efficient approach to control the magnetic state and dynamics in different classes of materials. Recent years, the crossover between two-dimensional van der Waals (2D vdW) materials and SOT opens a new prospect to push SOT devices to the 2D limit. In this mini-review, we summarize the latest progress in 2D vdW materials for SOT applications, highlighting the comparison of the performance between devices with various structures. It is prospected that the large family of 2D vdW materials and numerous combinations of heterostructures will widely extend the material choices and bring new opportunities to SOT devices in the future.